The meaning of ’justice’ in international trade: a problem of global justice - Guariglia, Osvaldo (Estudios de Filosofía, 2008)
Over the last century, some other social and political conditions were incorporated into natural conditions, decisively influencing the formation of at least three different groups of countries: developed countries, developing countries, and less developed countries. The 1947 GATT Agreement already admitted the existence of a wide gap between the three groups of countries and proposed additional measures to bridge that gap. [Fragment]